2019
DOI: 10.1002/bit.26996
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome and proteome analysis of steady‐state in a perfusion CHO cell culture process

Abstract: Long‐term continuous protein production can be reached by perfusion operation. Through the continuous removal of waste metabolites and supply of nutrients, steady‐state (SS) conditions are achieved after a certain transient period, where the conditions inside the reactor are not only uniform in space but also constant in time. Such stable conditions may have beneficial influences on the reduction of product heterogeneities. In this study, we investigated the impact of perfusion cultivation on the intracellular… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 43 publications
0
7
0
Order By: Relevance
“…Similar work reported by Vodopivec et al (2019) compared intracellular metabolomics of different growth phases among three bioreactors scales (10 L, 100 L, and 1000 L) to observe the scale-up effect [20]. As well as the studies in fed-batch cultures, Bertrand et al (2019) applied transcriptomics and proteomics to investigate the influence of long-term perfusion cultivation on the physiological state in an industrial CHO cell line [21]. Overall, omics approaches have contributed to deciphering the complicated CHO cell metabolism better and have aided in the identification of targets for rational genetic engineering and process optimization [22].…”
Section: Introductionmentioning
confidence: 54%
“…Similar work reported by Vodopivec et al (2019) compared intracellular metabolomics of different growth phases among three bioreactors scales (10 L, 100 L, and 1000 L) to observe the scale-up effect [20]. As well as the studies in fed-batch cultures, Bertrand et al (2019) applied transcriptomics and proteomics to investigate the influence of long-term perfusion cultivation on the physiological state in an industrial CHO cell line [21]. Overall, omics approaches have contributed to deciphering the complicated CHO cell metabolism better and have aided in the identification of targets for rational genetic engineering and process optimization [22].…”
Section: Introductionmentioning
confidence: 54%
“…Quantitative SPS-MS 3 based LC-MS analysis yielded excellent reproducibility with improved proteome coverage (Bertrand et al, 2019;Lakshmanan et al, 2019) and accurate quantification of proteins (Figure 3) without the need of intense fractionation (Heffner et al, 2017). Statistical data analysis by means of PCA (Figure 4C) indicated that the cellular effects underlying an improved antibody expression at low temperature and low pH differ considerably.…”
Section: Discussionmentioning
confidence: 99%
“…In another study, a single-use fluidic components-based perfusion bioreactor system was developed and enabled the implementation of active environmental control (Bournonville et al, 2019). In a study by Bertrand et al (2019), the impact of perfusion cultivation on the intracellular physiological state of a CHO cell line was investigated, revealing decreased mAb productivity as well as a transition phase for metabolites and product quality before reaching steadystate conditions. For viral vaccine production using anchoragedependent cells (e.g., Vero cells), microcarriers are necessary in the bioreactor.…”
Section: Transgenic Animalsmentioning
confidence: 99%